Nutritional Genomic: A Multi-Directional Approach to Address Complex Diseases with Multi-Functional Nutrition - Marta González-Castejón; Arantxa Rodriguez-Casado Madrid (Journal of Pharmacy and Nutrition Sciences, 2011)
Nutritional genomics describes the biological interactions between genes and diet, their effects on the metabolism, and susceptibility to develop diseases. This approach covers both nutrigenomics that explores the effects of nutrients on the genome; and nutrigenetics that explores the effects of genetic polymorphisms on diet/disease interactions. These interactions vary because individuals have unique combinations of common genetic polymorphisms that are differentially affected by diet. Diseases causality is associated to certain genetic polymorphisms providing predictive biomarkers for diagnostic accuracy. Specific nutrient can modify the expression of genes through the interaction with receptors that activate the transcription of target genes and affect signal pathways. Nutritional genomics is aimed to prevent onset of diseases and maintain human health, identify individuals who are responders and can benefit from specific dietary interventions, and identify how genetic variation affects human nutritional requirements. Nutritional genomics has many potential therapeutic and preventive applications: in individuals with a genetic predisposition to complex diseases including cancer, diabetes and cardiovascular disorders; in those already suffering from these diseases; and in those with memory impairment during aging. This review describes nutritional facts linked to genomic aspects to manage multigenic diseases. It presents some notable example of nutrients with proven modulating gene activity, and the role of nutrition associated with nutritional genomics. Hereafter we briefly review the health-promoting properties of two well-known edible plants, i.e. dandelion and artichoke whose presence in the diet could simultaneously exert positive influence on molecular genomic mechanisms related to risk factors for chronic diseases.